Efeito da vazão de ar e dos ciclos de aeração intermitente na remoção simultânea de carbono e nitrogênio em um reator de leito estruturado - Oliveira, Eduardo Paniguel (2019)
Between the new system configurations that remove organic matter and nitrogen simultaneously, there is the structured bed reactor with recirculation and intermittent aeration (SBRRIA). The SBRRIA has shown high efficiency of organic matter and nitrogen removal, besides the low sludge production. However, operational parameters, as the recirculation rate, aeration time and airflow, are not fully established. Thereby, the objective of this research was to evaluate the effect of these three parameters on the efficiency of organic matter removal and nitrogen removal in a SBRRIA. Hydrodynamic tests were done using salt as tracer and the variables were the recirculation rate, aeration time and airflow. It was determined that the reactor had a plug-flow behavior when the aeration was off, and it behaved as a completely stirred reactor when the aeration was turned on, independently of the airflow and recirculation rate tested. In this way, the biological operation of the reactor was started without internal recirculation, since this parameter was not necessary to guarantee the mixing in the reactor. The synthetic effluent applied to the reactor simulated the characteristics of sanitary sewage. The reactor was operated for 280 days with an operational hydraulic residence time (HRT) was 10 hours and it was operated inside a chamber with controlled temperature at 30˚C. Eleven tests were performed, varying the aeration time and the airflow rate. The COD removal was higher than 81% for all tests and the nitrogen removal varied from 10 to 80%. The higher efficiencies were obtained with aeration time of 1h45min (from a cycle of 3 hours) and airflow rate equals to 4,5L.min-1. Different nitrification and denitrification behavior were observed, obtaining efficiencies above 90% of nitrification when the reactor was submitted to higher aeration times and denitrification values above 90% when the reactor was submitted to low aeration times. Concluding, the studied variables showed to be significant in the efficiency response of the SBRRIA.